FA-3 Production Trait of Crossbreed Cattle and Reproductive Disorders in Brahman Cross (BX) Breeding Program at PT Lembu Jantan Perkasa - Berlin Pandapotan Pardede; Bakti Tamba; Sutrisnak Sutrisnak; I Ketut Karya Wisana; Harianto Budi Rahardjo; Muhammad Agil; Tuty L Yusuf (Hemera Zoa, 2018)
The feedlot industry in Indonesia has developed very rapidly, along with the increase in meat consumption. Brahman Cross (BX) is an imported beef cattle from Australia which is widely used by feedloters as broodstock. Feedloter chooses BX cattle because besides the price is quite cheap, this breed also has a very good growth factor [1].In order to support the self-sufficient of beef meat, feedloters who imported BX from Australia have to conduct breeding program as part of the Ministry of Agriculture decree no. 02/PERMENTAN/PK.440/2/2017 related to the import of ruminants into Indonesia. BX Cattle is often crossed with other breeds through artificial insemination programs, in order to provide calving ease and to produce high-weight cattle.Beside the target to produce good body weight and average daily gain (ADG) of the calf from crossbreeding, the feedloters have also to manage the breeding efficiently by taking care of the reproductive disorder that might be affected the production. Good reproductive efficiency will have a positive impact on increasing livestock production [2]. In various breeding programs, there are many factors that can affect the reproductive efficiency of cattle, such as reproductive disorders. Reproductive disorders can be a major economic problem in a farm. These reproductive health problems can be the bottleneck in the production process and productivity in the livestock sector [3].Therefore, this study will discuss the production performance in various cross-breed cattle and reproductive disorders in a feedlot breeding program.